Deferred autologous stem cell transplantation in systemic AL amyloidosis - Manwani, Richa; Hegenbart, Ute; Dittrich, Tobias; Kimmich, Christoph; Schönland, Stefan (Blood cancer journal, 2018)
High-dose melphalan with autologous stem cell transplantation (ASCT) can induce durable haematological and organ responses in systemic AL amyloidosis (AL). Stringent selection criteria have improved safety of ASCT in AL but most patients are transplant-ineligible. We report our experience of deferred ASCT in AL patients who were transplant-ineligible at presentation but had improvements in organ function after induction chemotherapy, enabling them to undergo ASCT. Twenty-two AL patients underwent deferred ASCT from 2011 to 2017. All had serial organ function and clonal response assessment. Organ involvement and responses were defined by amyloidosis consensus criteria. All patients were transplant-ineligible at presentation, predominantly due to advanced cardiac involvement. All received bortezomib-based therapy, with 100% haematologic response (86% complete response (CR)/very good partial response (VGPR)), enabling reversal of ASCT exclusion criteria. Patients underwent deferred ASCT for haematologic progression (45%) or consolidation (55%). There was no transplant-related mortality. Haematologic responses post-ASCT: CR 50%, VGPR 27%, PR 18%, non-response 5%. In all, 85.7% achieved cardiac responses. Median overall survival (OS) was not reached. Median progression-free survival (PFS) was 54 months. This selected cohort achieved excellent haematologic responses, organ responses, PFS and OS with deferred ASCT. If larger studies confirm these findings, this may widen the applicability of ASCT in AL.
Gesehen am 11.10.2019